The 2007 Rift Valley fever outbreak in Sudan. - Osama Ahmed Hassan; Clas Ahlm; Rosemary Sang; Magnus Evander (Public Library of Science (PLoS), 2011)
Rift Valley fever (RVF) is a neglected, emerging, mosquito-borne disease with severe negative impact on human and animal health and economy. RVF is caused by RVF virus (RVFV) affecting humans and a wide range of animals. The virus is transmitted through bites from mosquitoes and exposure to viremic blood, body fluids, or tissues of infected animals. During 2007 a large RVF outbreak occurred in Sudan with a total of 747 confirmed human cases including 230 deaths (case fatality 30.8%); although it has been estimated 75,000 were infected. It was most severe in White Nile, El Gezira, and Sennar states near to the White Nile and the Blue Nile Rivers. Notably, RVF was not demonstrated in livestock until after the human cases appeared and unfortunately, there are no records or reports of the number of affected animals or deaths. Ideally, animals should serve as sentinels to prevent loss of human life, but the situation here was reversed. Animal contact seemed to be the most dominant risk factor followed by animal products and mosquito bites. The Sudan outbreak followed an unusually heavy rainfall in the country with severe flooding and previous studies on RVF in Sudan suggest that RVFV is endemic in parts of Sudan. An RVF outbreak results in human disease, but also large economic loss with an impact beyond the immediate influence on the directly affected agricultural producers. The outbreak emphasizes the need for collaboration between veterinary and health authorities, entomologists, environmental specialists, and biologists, as the best strategy towards the prevention and control of RVF.